IRFBEN method for solving higher order differential equations - et. al., Emen . A . Hussain, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper provides a computational method for approximating a radial basis function networks (RBFNS) are used to model a function and its derivatives (scattered data interpolation), The solution of differential equations of the fourth order Kuromoto-Sivashansky Eq and Nikolaevsky equation of the sixth order is presented in this article. It could begin with a fourth-order derivative method. a RBFN is used to approximate the fourth order derivative. Integration yields the derivative of the third degree, then the derivative of the second degree, and finally the derivative of the first degree. Finally, the original function is derived in the same way, i.e. the derivative can be performed on a sixth-order equation using IRBFN.